TES PERFORMA DAN KECERDASAN MAJEMUK - Pribadi, Benny Agus; Lestari, Sri (Jurnal Pendidikan, 2011)
Learning paradigm had been shifted to "student centered in which teacher or instructor role is more as facilitators who help students develop optimal potential. In order to be effective teacher needs to better understand all potentials of students. One form of the potential is multiple intelligences. To determine the learning achievement, the assessment should cover multiple intelligence-based learning outcomes which are performance tests. Variety of performance tests can be used to assess the actual performance or learning outcomes achieved by students.